Mitigating the effects of cyberbullying crime: A multi-faceted solution across disciplines - Hamuddin, Budianto; Rahman, Fathu; Pammu, Abidin; Baso, Yusring Sanusi; Derin, Tatum (International Journal of Innovative Research and Scientific Studies, 2023)
The issue of cyberbullying is a social concern that has arisen due to the prevalent use of computer technology today. The objective of the present paper is to reveal a multi-faceted solution to cyberbullying across disciplines to mitigate the effects of this social problem. The purpose of this present study is to explore how researchers fight against cyberbullying across disciplines to create a systematic approach based on the primary health care approach based on the World Health Organization’s standard operating procedure, which consists of five types of primary care. This study is designed as a systematic literature review using Publish or Perish to automatically search through multiple databases to present the results of the keyword-based search and NVivo 12 to help understand the context. The study also uses conventional content analysis to categorize the areas of discipline and analyze the types of solutions offered in the collected 427 research articles on cyberbullying. Results have revealed that the largest major area is psychology, followed by IT media, education, and linguistics. The solutions recommended in the psychology area “plays” with a rehabilitative type of solution for cyberbullying; IT media solutions are largely the preventive type; the education area dominantly promotes “cyberkindness” to combat cyberbullying, and the linguistics area gives solutions that are curative for those involved in cyberbullying acts. Therefore, this research offers “beyond pre-venting” and might be the first study to recommend that WHO primary care can be used as systematic (four) steps to fight against cyberbullying.